Seasonal effects on proximal composition of male and female giant squid (Dosidicus gigas) and its rheological properties of surimi - Albrecht-Ruiz, Miguel (2017)
Giant squid adults of both sexes were used in different seasons. Grounded meat of each one were used to determine proximate composition, ammoniacal nitrogen, trimethyl amine contents, and viscosity. Simultaneously, surimi was prepared from each specimen to measure its gel strength. The moisture and protein values were between 81.2–86.9 and 10.5–16.4% respectively. They showed significant variations during summer in both sexes. The moisture: protein ratio was significantly lower in summer, showing greater variabilityamong males. When protein is transformed to a dry basis, differences between sexes are observed in winter and spring. Ammonia nitrogen was about 310.0 mg% and trimethylamine content was below 3.0 mg%. The apparent viscosity and gel strength values were significantly lower during winter, presenting males the lowest average values.